Shingaling [compact disc, unabridged] : a wonder story - Palacio, R. J. (Wonder story, 2015)
Listen about life as a fifth grader at Beecher Prep through the eyes of Charlotte, the girl who had been chosen to be Auggie's 'welcome' buddy. Listeners will not only learn more about Charlotte and her budding friendship with fan-favorite, Summer (they solve a mystery together), but how the girls at Beecher Prep react to Auggie attending their school for the first time.